2009
DOI: 10.1002/ccd.22035
|View full text |Cite
|
Sign up to set email alerts
|

Traditional antegrade approach versus combined antegrade and retrograde approach in the percutaneous treatment of coronary chronic total occlusions

Abstract: These results suggest that all CTO lesions should first be managed with an antegrade approach. When there is difficulty crossing the lesion, switching to a bilateral approach is an option for lesions with well-developed collaterals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Although the sheathless guiding catheters appear to provide better backup support, we should keep in mind again that the larger size of a guiding catheter might be more common with aortic dissection or donor vessel dissection. Major in-hospital events, including emergent bypass surgery or PCI, recurrent MI, stroke, cardiac tamponade and cardiac death, were similar to previous reports in CTO studies [18], [19], [20], [26], [27].…”
Section: Discussionsupporting
confidence: 87%
“…Although the sheathless guiding catheters appear to provide better backup support, we should keep in mind again that the larger size of a guiding catheter might be more common with aortic dissection or donor vessel dissection. Major in-hospital events, including emergent bypass surgery or PCI, recurrent MI, stroke, cardiac tamponade and cardiac death, were similar to previous reports in CTO studies [18], [19], [20], [26], [27].…”
Section: Discussionsupporting
confidence: 87%
“…However, computed tomography (CT) coronary angiography can reveal the calcification plaque as well as highlight the course of the coronary artery [7][8][9]. It has also been reported that severe calcifications are associated with more complications, low success rate, inadequate stent expansion, and high restenosis rate [9][10][11]. This study aimed to investigate the association between heavy calcification detected by CT coronary angiography and the result of intervention by 1 experienced operator.…”
Section: Introductionmentioning
confidence: 98%
“…To the best of our knowledge, a technique involving a bilateral ulnar approach has never been reported. We safely performed the PCI procedure with a radiation time quite comparable to the bilateral radial and femoral approaches described in the study of Hsu, et al 6) In the presented case report, both ulnar arteries were selected for access due to a smaller radial artery from pre-PCI physical examination, which was confirmed by peripheral hand injection through the arterial sheath. In our center, we predominately use "the arm approach"; 91.6% underwent PCI using a transradial approach, 3.5% through a brachial approach, 0.9% a transulnar approach, while the rest underwent a femoral approach.…”
Section: Discussionmentioning
confidence: 89%